CHATBOT AS ARTIFICIAL INTELLIGENCE LEARNING IN KNOWLEDGE MANAGEMENT - Lestari, Ambar Sri (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to create a chatbot as Artificial Intelligence learning in knowledge management.  The participants are teachers or lecturers engaging in the virtual education academic. Using machine learning technology on the https://m.chatboat.university platform, the result chatbot product development includes several steps, including: 1) using chatbot templates, 2) creating a self-contained chatbot. 3) modify the background and short description; 4) add chatbot content (image, text, video); 5) include quizzes and fun facts; and 6) create the chatbot design with thematic discussion. The development of the chatbot to provide students or users with a future learning that includes innovation, knowledge, learning community as displayed on the chatboat. This study has implications for learning innovation based on computational chatbots in interactive conversations as a transformation to support education in the 5.0 era.